Cytokine Profile of Mouse Vaginal and Uterus Lymphocytes at Estrus and Diestrus - Maria C. Lopez; Margaret A. Stanley (Clinical and Developmental Immunology)
It is known that sex hormones regulate IgA and IgG levels in the female reproductive tract. Moreover, antigen presentation by uterine and vaginal epithelial cells is also under strict hormonal control. The effect of the estrous cycle on cytokine secretion by vaginal and uterine lymphoid cells has been examined in mice using simultaneous staining for cytoplasmic cytokines and surface markers after ex vivo culture with PMA/ionomycin in the presence of Brefeldin A, and flow cytometry analysis. Two different mice strains, BALB/c and C57BL/6 mice, were used. The most relevant finding was the increase in the proportion of vaginal cells secreting IFN-γ at diestrus in both strains of mice. Other cytokines (IL-2 and IL-4) as well as some T cell subsets seemed to be modified in a strain dependent fashion. Data also suggest that NK cells are at least partially responsible for IFN-γ secretion. Our data indicate that vaginal and uterus lymphoid cells isolated at diestrus were in vivo activated to secrete cytokines after ex vivo culture. IFN-γ seems to be the key cytokine, since it increases in both strains of mice.